Estimate Zinc-Oxide Particles on PMMA Mechanical Properties - Saja Ali Muhsin; Israa Mohammed Hummudi; Makarem A.R. Al-Ani (Journal of Techniques)
Background: Poly-methylmethacrylate is the most used dental material for the construction of removable prosthodontic appliances. Unfortunately, it has shown to be lacking two important properties which are radio-opacity and mechanical strength. Zinc-oxide (ZnO) powder is widely used in dentistry and is considered a semiconductor material with the radio-opaque property.